Sites of action of Mojave toxin isolated from the venom of the Mojave rattlesnake - Gopalakrishnakone, P. (1980)
1 Mojave toxin isolated from the venom of the Mojave rattlesnake (Crotalus scutulatus scutulatus) produced an irreversible blockade of the contractile response of the mouse hemidiaphragm to stimulation of the phrenic nerve in vitro, at concentrations of 0.16 to 20 μg/ml; the response to direct stimulation was not affected over a testing period of several hours. 2 Mojave toxin (1 to 4 μg/g) was injected into the tail vein of mice and the intoxicated hemidiaphragm preparation was removed either for testing the contractile response or for intracellular recording. 3 In fully intoxicated hemidiaphragms the contractile response to indirect stimulation was either small and transient or absent, whilst the response to direct stimulation was well maintained. 4 Intracellular recording showed that resting membrane potentials of the muscle fibres were within the normal range. Endplates were difficult to locate but miniature endplate potentials (m.e.p.ps) were recorded at sites at which neurally evoked responses either could not be detected or did not exceed 2 mV which corresponds to transmitter release of a few quanta only. 5 The mean frequency of m.e.p.ps at fully intoxicated endplates was not significantly different from controls but potassium depolarization produced only a small increase in m.e.p.p. frequency relative to the control response. A 50 Hz tetanus had no effect on m.e.p.p. frequency. 6 When a sub-lethal dose (3 μg) of Mojave toxin was injected into one hindlimb of mice and the tissues examined at 72 h, there was histological evidence of myonecrosis. 7 The isolated perfused heart of the rat was exposed to recycled Mojave toxin (50 and 100 μg/ml) but showed no change in rate or force of ventricular contraction. 8 Post-mortem examination of intoxicated mice showed a frequent incidence of localized areas of interstitial and intra-alveolar haemorrhage in the lungs. Other organs including skin and muscle were not affected. 9 Mojave toxin showed antigenic similarities to crotoxin, the lethal neurotoxin in the venom of the South American rattlesnake, as determined by the ability of antiserum raised against crotoxin to neutralize Mojave toxin. 10 With systemic Mojave intoxication of rapid onset, the cause of death was respiratory paralysis. However, the toxin acts at multiple sites at differing rates of action. With a slower rate of intoxication, impaired respiration may act synergistically with cardiovascular changes to produce circulatory failure. The desirability of using an antivenin with a high titre against Mojave toxin is indicated.